I Feel Like I Am Flying and Full of Life: Contemporary Dance for Parkinson’s Patients - Bar, Anat; Czamanski-Cohen, Johanna; Federman, Judith Dita (Frontiers in Psychology, 2021)
Parkinson's is a neurodegenerative disease characterized by motor and non-motor symptoms which are strongly associated with patients' quality of life, affecting social skills and support. It strikes not only the motor abilities but may harm cognitive and emotional functioning. For the past 15 years, contemporary dance has been employed as an intervention to help people diagnosed with Parkinson’s disease cope physically and mentally by way of motor, vestibular, and sensory stimulation as well as social interaction. In this study we aimed to examine psychological flexibility, creative self-efficacy and quality of life of Parkinson's patients participating in contemporary dance sessions. To obtain this goal we conducted a cross-sectional comparative study of 50 Parkinson's patients aged 50–87 years, half of which had been participating for at least three months once a week, in contemporary dance classes, and the matched controls participated in a verbal support group. Study participants completed questionnaires after participating in a dance class (Intervention) or in a support group (control). Participants in the intervention group were also asked to answer three open-ended questions that examined the experience of participating in contemporary dance classes. We found that psychological flexibility and quality of life were significantly higher in the dance class participants. Participants reported positive changes that occur in their overall feeling and quality of life following their participation in dance classes. Since PD patients’ experiences are deeply embedded in the body, it is significant to explore the use of movement in treatment. The importance of the study is in its potential to highlight the relationship between psychological flexibility and quality of life and to increase awareness of clinicians treating Parkinson's patients to the importance of incorporating dance as an inherent part of a multidisciplinary team effort.